Clinical characteristics of COVID-19 in children: a large multicenter study from Iran - Hajialibeig, Azin; Navaeifar, Mohammad Reza; Bordbari, Amir-Hassan; Hosseinzadeh, Fatemeh; Rostami-Maskopaee, Fereshteh; Rezai, Mohammad Sadegh (Frontiers in Pediatrics, 2024)
During the COVID-19 pandemic, pediatric cases typically exhibit milder symptoms and lower mortality rates. However, the delay in pediatric vaccination poses major risks for children. This multicenter study aimed to comprehensively analyze demographic characteristics, clinical features, disease severity, and risk factors for ICU admission in Iran. This observational study enrolled children aged 0-21 years with confirmed or probable COVID-19 diagnoses, referred from selected hospitals across 17 counties in Mazandaran province, Iran, between February 19 and August 14, 2021. Patients were categorized into mild, moderate, severe, or critical cases based on clinical and radiographic criteria. Data were extracted from medical records and analyzed using statistical methods. Logistic regression analysis was performed to identify factors associated with ICU admission and disease severity. Among the 1,031 children included in the study, 61 were diagnosed with MIS-C. The distribution of patients by severity was 156 mild, 671 moderate, and 204 severe/critical cases. Age distribution significantly differed across severity groups (P<0.001), with 55.19% aged over 5 years and 54% being male. 11.44% had underlying diseases. Fever (71.97%) was the most common symptom, followed by cough (34.43%) and dyspnea (24.83%). Within the inpatient group, 19.77% required ICU admission, with 0.91% mortality, including 3 MIS-C cases. Children with underlying diseases, gastrointestinal symptoms, and obesity had 4.16, 3.10-, and 2.17-times higher likelihood of ICU admission, respectively. Our study emphasized the importance of recognizing pediatric COVID-19 severity and symptoms. While fever, cough, and dyspnea prevailed, mortality rates were relatively low. However, comorbidities, obesity, and gastrointestinal symptoms linked to ICU admission, stressing early intervention. BMI also impacted disease severity and admission rate. Vaccination and targeted interventions are essential for protecting vulnerable children and easing healthcare strain.